RESIDENTS’ PERCEPTIONS OF GAY TOURISM: EXPLORING ATTITUDES, SEXUAL PREJUDICE AND DISCRIMINATION, AND PLACE IMAGE - Rahmat Satria Harmi; Febrian Nur Ramadhan; M Rasyid Fauzirin; Roozbeh Babolian Hendijani (RADJA PUBLIKA, 2026)
While numerous studies have explored residents’ attitudes towards tourism in general, limited research exists on their perspectives towards gay tourism, especially in non-Western contexts. Most existing studies focus on Western countries, where there is generally higher acceptance of homosexuality, overlooking majority Muslim countries. Residents’ attitudes towards tourism are believed to be key factor in the sustainability of tourism development. This study aims to investigate the residents’ attitudes towards gay tourism. This study investigates residents’ attitudes towards gay tourism, focusing on the influence of place image, perceived impacts, and sexual prejudice. The study finds a significant positive relationship between perceived economic and socio-cultural impacts and residents’ supportive attitudes towards gay tourism. However, no correlation is found between place image and attitudes, while sexual prejudice and discrimination play a role in shaping negative attitudes towards gay tourism. This research provides an analysis of the perceptions of gay tourism among residents by incorporating, for the first time, the variables of place image and sexual prejudice toward tourism and cultural studies.